The Muradiye and Imaret mosques in the context of early Ottoman Filibe: Two case studies - Chardakliyska, Elena (AUC Knowledge Fountain, 2006)
The two mosques remaining in present-day Plovdiv, Bugaria or Ottoman Filibe are the Muradiye and Imaret mosques. The Murndiye Mosque, also known as the Ctm1a (or Friday) mosque built in ca. 1435 and the Imaret Mosque, founded in 1444, represent an important period of the history of the town vis-a-vis its transformation into an important urban center in the Ottoman province of Rumeli. The Imaret Mosque is an example of a reserve T-shaped imnret/zaviye which was surrounded by a charitable complex. It is also the monument whose study is more challenging because of the uncertainties posed by its changing functions. By exploring at the monuments as they stand today, this thesis aims to come to an understanding of the nature of the urban growth and changes, which occurred in the second half of the 15th century. The monuments and their contexts are studied at the intersection of two seemingly divergent approaches-the first one calls for the close examination of the monument, botl1 historic and architectural, while the other looks at the patterns of conquest and settlement, the most commonly applied architectural styles and their distribution in other urban centers in the Ottoman Empire pre-1453. The first approach takes into consideration architectural interventions and aims to find visual evidence for what the original forms of the monument must have been like. Archival photographs have been employed to enhance our understanding of the last century in the buildings' histories. The two mosques serve as evidence in rephrasing dichotomies such as center-periphery and imperial-provincial and allow not only for an entry point through which to explore Ottoman Filibe in the I 5th century but also for understanding the early Ottoman Empire and its connection to the Balkans and Rumelia.